2016
DOI: 10.1200/jco.2016.66.7162
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plasma Genotyping and Outcomes of Treatment With Osimertinib (AZD9291) in Advanced Non–Small-Cell Lung Cancer

Abstract: Purpose Third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) have demonstrated potent activity against TKI resistance mediated by EGFR T790M. We studied whether noninvasive genotyping of cell-free plasma DNA (cfDNA) is a useful biomarker for prediction of outcome from a third-generation EGFR-TKI, osimertinib. Methods Plasma was collected from all patients in the first-in-man study of osimertinib. Patients who were included had acquired EGFR-TKI resistance and evidence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
668
9
10

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 762 publications
(729 citation statements)
references
References 19 publications
35
668
9
10
Order By: Relevance
“…Limitations of plasma assays include decreased sensitivity compared with tissue testing, and results can be dependent on tumor volume and the sites of disease (14). Similar to tissue molecular genotyping, EGFR mutations identified within plasma serve as biomarkers that predict response to EGFR TKI treatment (12,15,16). Plasma assays of EGFR exon 19 deletions (ex19del), EGFR L858R, and T790M point mutations are now approved for clinical use (17).…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of plasma assays include decreased sensitivity compared with tissue testing, and results can be dependent on tumor volume and the sites of disease (14). Similar to tissue molecular genotyping, EGFR mutations identified within plasma serve as biomarkers that predict response to EGFR TKI treatment (12,15,16). Plasma assays of EGFR exon 19 deletions (ex19del), EGFR L858R, and T790M point mutations are now approved for clinical use (17).…”
Section: Introductionmentioning
confidence: 99%
“…In addition Oxnard et al showed that outcomes of T790M-positive patients included in the phase I AURA study were similar if T790M was detected in plasma or tumor tissue. Conversely both RR and PFS of T790M-negative patients on plasma were significantly higher than T790M-negative on tissue, and further tumor genotyping of plasma T790M-negative patients allowed to identify a subgroup of T790M-positive patients on tumor tissues who had better outcomes (Oxnard et al, 2016). According to these data the authors suggest that plasma genotyping could represent the first step for the detection of T790M status at the time of PD.…”
Section: Potential Application At Progressionmentioning
confidence: 89%
“…Recently his group prospectively evaluated the sensitivity and specificity of plasma genotyping by ddPCR in 180 patients with advanced NSCLC, including 60 patients with acquired resistance to EGFR-TKI. Plasma genotyping by ddPCR exhibited 79% specificity and 77% sensitivity in the detection of T790M mutation, which are lower than those observed with EGFR-activating mutations at baseline (Oxnard et al, 2016). In addition Oxnard et al showed that outcomes of T790M-positive patients included in the phase I AURA study were similar if T790M was detected in plasma or tumor tissue.…”
Section: Potential Application At Progressionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although tumor tissue samples remain the gold standard for cancer mutation testing, novel methods of testing are emerging that are less invasive, including those based on cytology samples and ctDNA which should be considered for patients who are ineligible for a tissue biopsy. Various studies support the use of plasma ctDNA samples for the detection of EGFR mutations at diagnosis of NSCLC, including data from the recent AURA (AURA extension, AURA2, and AURA3) and FLAURA studies [18,31,32,17]. The phase I AURA post-hoc analysis (NCT01802632) found that, in patients with advanced NSCLC and EGFR T790M-positive status (according to central tumor genotyping), the sensitivity of plasma ctDNA samples for the detection of T790M was 70% [32].…”
Section: Discussionmentioning
confidence: 99%